Parking Assistance with ATMega16 Microcontroller - Dea Rizki Febrianti Tawakal; Erwin Sitompul (President University, 2016)
Nowadays safety becomes an increasing important factor in developing cars. Measures come in the form of physical strengthening and diagnostics improvement of the car. One way to improve the safety of a car is by implementing a car parking assistance. Although it already becomes a standard feature in some cars, the additional charge for the customers is still considerably high. This condition motivates the author to develop and implement a car parking assistance with affordable price and suitable for any types of car. The proposed system utilizes the ATmega16 Microcontroller and an ultrasonic sensor. The ultrasonic has a transmitter that produces a pulse in every 62.5 ms, and a receiver that detects the reflected pulse. The time of wave travel and thus the distance can be deduced. An LCD and a LED indicate the presence of object in front of the ultrasonic sensor. The resulting prototype proved that a car parking assistance can be made with low cost. Besides, it can be installed in any car with minimal adjustment.